The role of lncRNA MALAT1 in cardiovascular disease. Issue 3 (19th December 2019) - Yan, Youyou; Song, Dandan; Song, Xianjing; Song, Chunli
Abstract: Cardiovascular disease (CVD) is the first leading cause of death worldwide. Understanding the molecular mechanism of signaling pathways involved in pathology of CVD is benefit for targeted therapeutics. Recently, long non‐coding RNAs (lncRNAs) are found and involved in regulation of pathology of CVD at different levels. Among them, MALAT1 attracted more attention as it was profoundly expressed in endothelial cells or cardiomyocytes in response to the risk factors of CVD, such as hypoxia, high glucose, cytokine, and oxidative stress. In this review, we summarize recent progresses in research on the molecular mechanism of MALAT1 on regulating the pathophysiological processes of CVD as well as its potential therapeutic applications.